Feasibility analysis of salt cavern gas storage in extremely deep formation: A case study in China. (March 2022) - Zhao, Kai; Liu, Yuanxi; Li, Yinping; Ma, Hongling; Hou, Wei; Yu, Changfu; Liu, Haolin; Feng, Chang; Yang, Chunhe
Highlights: A 3D geo-mechanical model was established to study the long-term stability of the potential ultra-deep salt cavern. Constructing salt cavern gas storage in an extremely deep formation (more than 2700 m) is feasible. The critical engineering issues for constructing salt cavern gas storage in an extremely deep formation are discussed. Abstract: The depth of the underground salt cavern for the storage of hydrocarbons mainly ranges from 500 to 1500 m. The target formation of the Ningjin salt district, Hebei province, China, for constructing a salt cavern gas storage is more than 2700 m in depth, which will be the deepest salt cavern worldwide. This study comprehensively analyzed the feasibility of storing natural gas in an extremely deep salt cavern. Hydraulic fracturing tests and the anelastic strain recovery (ASR) method were performed to measure the in-situ stress. Laboratory tests including uniaxial and triaxial compression, Brazil disk splitting, triaxial creep and permeability were conducted on cores to obtain their mechanical parameters. The target salt layer for constructing the salt cavern gas storage was determined. The cavern shape, dimension and operating gas pressure of the potential salt cavern were designed accordingly. A 3D geomechanical model was established to investigate the long-term stability of the salt cavern based on the geologic structure. An integrated index system was used to assess the cavern stability over the long term quantitatively. Simulation results show that the internal gas pressure is the critical parameter affecting the cavern stability, and 28 MPa is the lowest internal gas pressure to satisfy the stability requirement. Comprehensive analysis indicates that storing natural gas in an extremely deep salt cavern is feasible. The shrinkage in the open hole section should be accounted for, and no cushion gas technology is suggested to improve the economic benefits.